RTOG‐0129 risk groups are reproducible in a prospective multicenter heterogeneously treated cohort. Issue 19 (18th June 2021) - Fakhry, Carole; Tewari, Sakshi R.; Zhang, Lisa; Windon, Melina J.; Bigelow, Elaine O.; Drake, Virginia E.; Rooper, Lisa M.; Troy, Tanya; Ha, Patrick; Miles, Brett A.; Mydlarz, Wojciech K.; Eisele, David W.; et al.
Abstract : Background: Recursive partitioning analysis (RPA) from the Radiation Therapy Oncology Group (RTOG)‐0129 has identified a low‐risk group of patients with oropharynx cancer (OPC) who might benefit from therapeutic de‐intensification. These risk groups have not yet been reproduced in an independent cohort treated heterogeneously. Therefore, the objective of this analysis was to validate the RPA risk groups and examine the prognostic impact of novel factors. Methods: Patients with OPC were enrolled in a prospective study at 3 academic medical centers from 2013 to 2018. Medical record abstraction was used to ascertain clinical variables including staging and survival according to the 7th edition of the American Joint Committee on Cancer ( AJCC ) Cancer Staging Manual . Human papillomavirus–positive tumor status was determined by p16 immunohistochemistry and/or HPV RNA in situ hybridization. Kaplan‐Meier and log‐rank methods were used to compare survival. Cox proportional hazards were used to generate univariate and multivariable hazard ratios (HRs). Results: Median follow‐up time was 3.2 years. The low‐, intermediate‐, and high‐risk groups had significant differences in 2‐year overall survival (OS, 99.1%; 95% CI, 94.4%‐99.9% vs OS, 93.0%; 95% CI, 74.7%‐98.2% vs OS, 80.0%; 95% CI, 40.9%‐94.6%; P overall = .0001) and 2‐year progression‐free survival (PFS, 97.5%; 95% CI, 92.4%‐99.2% vs PFS, 89.3%; 95% CI, 70.3%‐96.4% vs PFS, 80.0%; 95% CI, 40.9%‐94.6%; P overall < .002). After adjustment for age, sex, and level of educational attainment, OS and PFS were significantly lower for the intermediate‐ (OS adjusted hazard ratio [aHR], 5.0; 95% CI, 1.0‐23.0; PFS aHR, 3.4; 95% CI, 1.0‐11.5), and high‐ (OS aHR, 7.3; 95% CI, 1.4‐39; PFS aHR, 5.0; 95% CI, 1.2‐21.6) risk groups compared with the low‐risk group. Lower education was also independently significantly associated with worse OS (aHR, 8.9; 95% CI, 1.8‐44.3) and PFS (aHR, 3.1; 95% CI, 1.0‐9.6). Conclusions: In patients with OPC, the RTOG‐0129 RPA model is associated with OS and PFS in a heterogeneously treated cohort. Abstract : In patients with oropharyngeal squamous cell carcinoma (OPC), the Radiation Therapy Oncology Group (RTOG)‐0129 recursive partitioning analysis model is associated with overall survival and progression‐free survival in a heterogeneously treated cohort. It is the hope that this study will contribute to identifying favorable, low‐risk patients with therapeutic implications for treatment de‐intensification in future clinical trials for OPC.